Subjetividade nas setenças judiciais: uma análise semântico-pragmática dos modalizadores - Silva Júnior, Adiniz Mendes da (2012)
The present work has as its main aim studying how the manifested speakers subjectivity, the law judge s one, through the analysis of the many types and sub-types of modalization, identifying, describing and analyzing the semantic-pragmatic effects of modalizers in criminal sentences. Our problematization laid on the following question: how is the subjectivity manifested during the judges speeches, the ones who perform the criminal sentences, and the use of modalizers, real subjectivity speech marks, in a discourse genre which shows the distance the speaker has? Our claim is that the modalizers are current semantic-discursive strategies used in judicial sentences, expressing judges discursive proximity and distance arising from the tension the genre itself creates and from the need of impartiality. In order to reach our aims, we took as a theoretical reference the studies about modalization of authors like Castilho e Castilho (1992), Cervoni (1989), Coracini (1991), Koch (1996), Nascimento (2005), Neves (1997; 2006; 2011), Palmer (1991), Silva (2007) and also the studies about the argumentative theory from Ducrot e Anscombre (1988). We decided to work with a corpus composed eight (08) criminal sentences, stated by the Ministério Público , which are on Internet on the web page of Escola Judicial Desembargador Edésio Fernades-EJEF, of Tribunal de Justiça do Estado de Minas Gerais. We tried to analyze the sentences of different crimes, decreed by different judges, which six of them sentencing and two acquittals. This research is a descriptive-interpretative one through a qualitative approach. Though we have count the cases of modalization, we searched for the meanings in the modalized chunks and their relation with the immediate context: the speaker, the discursive genre, the interlocutors and the discourse aim. Our analyses showed that our hypothesis was true. There is a great incidence of modalizers in the judicial text arrangement, including in the three parts: report, fundamentation and dispositive. In fact, the speaker is marked in the sentences, indicating its views, opinions, driving understandings, denying some others, etc. and the modalization is mainly responsible for that.